1999
DOI: 10.1007/bf02329805
|View full text |Cite
|
Sign up to set email alerts
|

Experimental examination of bicycle chain forces

Abstract: ABSTRACTmThis paper presents the results of an investigation evaluating the forces present in a statically loaded bicycle chain prior to and beyond sprocket engagement. Comparisons are made with previous investigations that have been limited to industrial chains and sprockets. The chain drive system for a bicycle differs from the industrial standard types not only in its size but in its operation. A high degree of lateral flexibility is required in the bicycle chain for it to operate with noncoplanar sprockets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Consequently, the fundamental arrives at the distal portion of the chain sooner than the second harmonic and, in doing so, alters the chain-sprocket interaction for the second harmonic by changing the orientation of the sprocket tooth relative to the link and decreasing the load transfer. Kidd et al modeled load transfer from chain to sprocket using the geometric progression load distribution (GPLD) method allowing for calculation of link tension during sprocket engagement/departure [4]. They also made static measurements of link tension as a function of angular orientation (sprocket relative to chain line) to confirm the validity of the GPLD model.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Consequently, the fundamental arrives at the distal portion of the chain sooner than the second harmonic and, in doing so, alters the chain-sprocket interaction for the second harmonic by changing the orientation of the sprocket tooth relative to the link and decreasing the load transfer. Kidd et al modeled load transfer from chain to sprocket using the geometric progression load distribution (GPLD) method allowing for calculation of link tension during sprocket engagement/departure [4]. They also made static measurements of link tension as a function of angular orientation (sprocket relative to chain line) to confirm the validity of the GPLD model.…”
Section: Introductionmentioning
confidence: 98%
“…Their estimates indicated that 96%-99% efficiency could be obtained for sprockets typically used for bicycles but no measurements of chain drive efficiency were presented. Kidd et al [4] modeled and measured forces in bicycle chain links during engagement and departure to provide information necessary to estimate efficiency but these models were not used to do so. Work by Lodge and Burgess [5] assessed the efficiency of bush roller chains, including bicycle chains, by modeling frictional losses and measuring efficiencies using a drive system that isolated losses in the chain drive itself.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidd et al. 11 studied the results of an investigation evaluating the forces present in a statically loaded bicycle chain prior to and beyond sprocket engagement. Sujata et al.…”
Section: Introductionmentioning
confidence: 99%
“…Sheu [12] proposed a vector approach for analyzing the friction kinetostatics and the transmission efficiency. The forces in the chain links were measured experimentally by Kidd et al [13] and showed that sprocket misalignment leads to localized bending of the chain links. Marshek et al [14] showed that the misalignment leads to rubbing of the links with the sprockets.…”
Section: Introductionmentioning
confidence: 99%